Screening of Active Compounds from Artemisia annua using HFC-134A Subcritic Extraction System - Arthur Lelono; Sabar Simanungkalit; Ibnu Umarudin; Herlan Herdiawan (Journal of Tropical Pharmacy and Chemistry, 2018)
Artemisia annua is known as the source of artemisinin, a sesqueterpene lactone possessing endoperoxide moeity with antiplasmodium activity. Sub-critical extraction of artemisinin from Artemisia annua using R134a solvent was conducted. A close system cycle process was constructed to investigate the ability of R134a to extract artemisinin together with other active compounds. Artemisinin and other isolated compouds yield was investigated at 30Â°C and presure process at 10 barr, with variation of process time. The extracted product was analysed as artemisinin as the target compounds with several isolated compounds as by product. Artemisinin content was reported ranging up to 0,5%, and the sub critic system was reported to be more efficient and effective comparing to other conventional extraction methods. The phytonics HFC-134a sub critics process can be used for extraction in selected pharmacologically active products from herbal plants.